Deformation and Failure Characteristics of Loading and Unloading Rock Based on Volume Crack Strain - Liu, Xiaohui; Zheng, Yu; Guo, Jinyun; Hao, Qijun; Xue, Yang (Frontiers in Earth Science, 2022)
In order to study crack evolution laws of rock and explain its fracture instability mechanism, a series of laboratory tests were carried out with Jinping Marbles. The test results show that failure degree of marbles under unloading condition is more severe than that under loading condition. Based on volume crack strain, five stages of progressive failure of crack evolution under different conditions are divided, and the corresponding characteristic stresses are determined. The pre-peak volume crack propagation strain without considering the initial damage is used to evaluate the pre-peak crack growth propagation of rock, it is found that the lower the confining pressure, the higher the strain rate and unloading rate, the less the cracks generated before peak, and rock is more prone to brittle failure after peak. The starting point of sharp increasing of volume crack strain rate is proposed as the failure precursor point, and stress levels of failure precursor of marbles are in 70-100%, which decrease with confining pressure, strain rate and unloading rate rising. Under unloading condition, failure precursor points appear later and are close to unloading point, and unloading rocks are more prone to sudden brittle failure.